If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(z + -1) = 2z + -4 Reorder the terms: 4(-1 + z) = 2z + -4 (-1 * 4 + z * 4) = 2z + -4 (-4 + 4z) = 2z + -4 Reorder the terms: -4 + 4z = -4 + 2z Add '4' to each side of the equation. -4 + 4 + 4z = -4 + 4 + 2z Combine like terms: -4 + 4 = 0 0 + 4z = -4 + 4 + 2z 4z = -4 + 4 + 2z Combine like terms: -4 + 4 = 0 4z = 0 + 2z 4z = 2z Solving 4z = 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. 4z + -2z = 2z + -2z Combine like terms: 4z + -2z = 2z 2z = 2z + -2z Combine like terms: 2z + -2z = 0 2z = 0 Divide each side by '2'. z = 0 Simplifying z = 0
| 3x-10=2x+4 | | 0=2/3-x | | 7+7(p-6)=-38+6p | | 13x=19-x^2 | | 7+7p(p-6)=-38+6p | | 3(x-1)-(x+4)=2x-7 | | 5x+5=5(x-1) | | .25x^2+x+7=0 | | Y+4=x^2-2x | | -4+3x=10 | | 5x+1=-(2x+13) | | Y-x^2=-20+8x | | 2a+1=6+11 | | Q=3P-4 | | 2x+34+3x= | | 2P=20-Q | | 9(4b-1)=2(b+3) | | x-42.041=23.24 | | 7x-3y=9 | | -4n+11=-4(n+6) | | 15a+2.75=6.20 | | Q=20-2P | | 12x+24+36x=90 | | -0.2x+y=12 | | 3+97-11=6 | | x=-49.5+5.5X | | 5(-6x+5)+3x=-3 | | 4q+2=48q | | 3+2y=-8 | | ydx+x(1-0.5xy)dy=0 | | -9x-4=-3(-2+3x) | | 16=2(x-6) |